Master Rowe and the origins of anthropological thinking - del Pino Díaz, Fermin (2018)
Rowe (1964) is, perhaps, who suggested before anyone - with a fine sense of historical time - that the Jesuit Acosta was the writer of Indias first establishing a temporal sequence in which some stages of cultural evolution ‘succession’ ones to others. The type present in the proem of his missionary treat ise (De Procuranda Indorum salute, 1588) is ‘historized’ only in his history of 1590, precisely to the encounter with Mexican traditions about his past by contrast chichimecas, which Acosta perceived as ‘parallel’ to Inca traditions about the ‘chunchos’ of the Andes. In the following year published Rowe a general reflection on ‘the Renaissance origins of Anthropology’ (American Anthropologist, 1965): what mattered in this discipline was having destroyed ethnocentrism Christian to see other cultures, and that the admiration and new translation of the Italian humanists of the 14th and 15th centuries the texts and classic monunentos, product of a non-Christian culture. I found a reef interpretation in these two articles (1964, 1965) to construct a building anthropological P. Acosta, affiliating with the current humanist rather than trusting their ethnographic data (mostly borrowed).